Clinical and demographic profile of recurrent headache in school-going children of Bundelkhand region, Central India - Kankane, Arvind; Kankane, Aradhana; Gupta, Sapna (Indian Journal of Child Health, 2019)
Introduction: Headache is one of the most common neurological disorders worldwide. Headache in school-going children have several specific characters as compared to adults. It is also important to determine region-specific variable for better and effective health planning. Aims and Objectives: The present study was conducted to determine the clinical and demographic profile of various headache types, in school-going children of Bundelkhand region, Central India. Materials and Methods: This prospective, questionnaire-based cross-sectional study was conducted in a tertiary care hospital of Bundelkhand region, Central India. The study included all school-going children between 5 and 18 years, fulfilling International Classification of Headache Disorders, 3rd edition diagnostic criteria for a primary headache who presented to the neurology and pediatric outpatient department. Sociodemographic and clinical details were collected and analyzed. Results: A total of 121 patients were included in the study, out of the 55% were male. Mean age of presentation to the hospital was 12.3±4.3 years and age of onset of headache disease was 8.9±3.8 years. Migraine and tension-type headache were found in 62.8% and 26.4%, respectively. The mean interval of onset to a presentation at headache clinic was 26.8±24.6 months. All of them were on self-medication or over the counter medications before the presentation. Conclusion: This study provides a clinical profile of a headache in school-going children of central India. Majority of them were presented late for medical attention.